Crack detection in PM-rotors using magnetic field measurement and data processing - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Herzog, Moritz; Franke, Jörg; Brela, Matthaeus (2017 7th International Electric Drives Production Conference, EDPC 2017 - Proceedings, 2018)
Electric drives efficiency is determined by the mechanical and magnetic properties of the functional elements stator and rotor. Focus element for this investigation is the rotor including its permanent magnets. Due to several manufacturing influences the properties of those magnets vary considerably. Magnet failures that can occur during manufacture are cracks, blowholes or inclusions, which can lead to commutation problems or to increased noise [1]. Crack propagation is a long-lasting process and cause unintentional failure in field. Currently no automated quality inspection of micro cracks is available in electric drive production. Consequently, the challenge is to develop reliable and safe process concept, to separate bad from good rotors based on magnetic field measurements in order to detect failures at the internal or external assembled magnets. For this purpose, a data analyzing method was developed to identify and characterize micro cracks in already assembled permanent magnets.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Crack Detection; Data Processing; Fault Detection; Magnetic Field Measurement; Permanent Magnet; Sensors